Factors Affecting Plant Composition in Abandoned Railway Areas with Particular Emphasis on Forest Proximity - Agnieszka Hutniczak; Alina Urbisz; Andrzej Urbisz; Łukasz Strzeleczek (Diversity, 2022)
Abandoned railway areas are places for the spontaneous spread of plants and the formation of specific plant communities. However, only limited information on this subject is available in the literature. The study aimed to determine the direction and the rate of forest formation, taking into account selected environmental factors. A floristic, phytosociological, and soil survey was carried out on a set of abandoned railway lines in the Silesia Province (southern Poland). For this purpose, 30 plots of vegetation were selected: 15 located in the vicinity of forests (F) and 15 surrounded by ruderal or segetal communities (NF). As a result, a total of 132 species (121 vascular plants and 11 mosses) were recorded, including 83 species at F plots and 78 species at NF plots. During the research, 13 syntaxa were distinguished. It was found that silt content, nitrate nitrogen (N-NO3), pH, and phosphorous have a significant impact upon which species dominated in the surveyed areas. It was found that the proximity of the forest was a crucial factor in determining the development of forest communities on abandoned railway areas. These results can be helpful for understanding how environmental conditions shape the forest structure on these types of habitats.